2018
DOI: 10.1080/00365521.2018.1500639
|View full text |Cite
|
Sign up to set email alerts
|

The impact of an adaptation course on health-related quality of life and functional capacity of patients with inflammatory bowel disease

Abstract: Adaptation training appears to have a positive impact on the psychological well-being of IBD patients. Peer support appears to be an important factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(35 citation statements)
references
References 28 publications
0
35
0
Order By: Relevance
“…A critical point of about 2 years after diagnosis being the moment when coping with IBD becomes easier was noted. Indeed, accepting the diagnosis may offer benefits to patients -previous uncontrolled research demonstrated good efficacy of an IBD adaptation course on psychological well-being (Haapamaki et al, 2018). More studies exploring disease acceptance in IBD populations are needed.…”
Section: Discussionmentioning
confidence: 99%
“…A critical point of about 2 years after diagnosis being the moment when coping with IBD becomes easier was noted. Indeed, accepting the diagnosis may offer benefits to patients -previous uncontrolled research demonstrated good efficacy of an IBD adaptation course on psychological well-being (Haapamaki et al, 2018). More studies exploring disease acceptance in IBD populations are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Social support, the sharing of concerns and experiences with family, friends and HCPs helps to maintain high levels of HRQoL (Lesage et al, 2011;Haapamäki et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The interventions were delivered in IBD centres as either outpatient or inpatient service ( n = 8) [ 33 37 , 40 , 46 ], in a local community centre ( n = 1) [ 44 ], in summer residential camps ( n = 3) [ 41 , 42 , 45 ], within university settings ( n = 1) [ 39 ] or the specific setting was not specified ( n = 1) [ 44 ]. All were based in high-income (European countries, USA, New Zealand) or upper middle-income countries (Brazil, Chile, and China).…”
Section: Study Characteristicsmentioning
confidence: 99%